Staphylococcus aureus vesicles impair cutaneous wound healing through p38 MAPK-MerTK cleavage-mediated inhibition of macrophage efferocytosis - Jiaxin Ou; Kangxin Li; Hui Yuan; Shaohua Du; Tingting Wang; Qiannan Deng; Huimei Wu; Weiyan Zeng; Kui Cheng; Kutty Selva Nandakumar (Cell Communication and Signaling)
Abstract Background Staphylococcus aureus, a known contributor to non-healing wounds, releases vesicles (SAVs) that influence the delicate balance of host-pathogen interactions. Efferocytosis, a process by which macrophages clear apoptotic cells, plays a key role in successful wound healing. However, the precise impact of SAVs on wound repair and efferocytosis remains unknown. Methods Filtration, ultracentrifugation, and iodixanol density gradient centrifugation were used to purify the bacterial vesicles. Transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Western blot (WB) were used to characterize the vesicles. Macrophage efferocytosis efficiency was assessed using flow cytometry and confocal microscopy, while efferocytosis at wound sites was analyzed through WB, FACS, and TUNEL staining. Hematoxylin and eosin (H&E) staining and wound size measurements were used to evaluate the wound healing process. Phosphorylation of signaling pathways was detected by WB, and efferocytosis receptor expression was measured using RNA sequencing, qPCR, and flow cytometry. siRNA and pathway inhibitors were used to investigate the roles of key receptors and signaling pathways in efferocytosis. Results We identified SAVs at infected wound sites, linking them to delayed healing of wounds. SAVs inhibit efferocytosis by activating the TLR2-MyD88-p38 MAPK signaling pathway, which regulates efferocytosis receptor genes. This activation promoted cleavage and shedding of MerTK, a crucial receptor for macrophage-driven efferocytosis. Notably, selective inhibition of p38 MAPK prevented MerTK shedding, restored efferocytosis and accelerated wound healing significantly, offering a promising therapeutic approach for chronic, non-healing wounds. Conclusion These findings uncover a novel mechanism in S. aureus-infected wounds, highlighting how the disruption of efferocytosis via the TLR2-MyD88-p38 MAPK-MerTK axis becomes a key force behind impaired healing of wounds. Targeting this pathway could open up a new therapeutic avenue facilitating the treatment of chronic, non-healing skin injuries.